2016
DOI: 10.1093/gbe/evw137
|View full text |Cite
|
Sign up to set email alerts
|

Complex Selection on Human Polyadenylation Signals Revealed by Polymorphism and Divergence Data

Abstract: Polyadenylation is a step of mRNA processing which is crucial for its expression and stability. The major polyadenylation signal (PAS) represents a nucleotide hexamer that adheres to the AATAAA consensus sequence. Over a half of human genes have multiple cleavage and polyadenylation sites, resulting in a great diversity of transcripts differing in function, stability, and translational activity. Here, we use available whole-genome human polymorphism data together with data on interspecies divergence to study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…Our in silico analysis revealed that the poly(A) cleavage site of NTO2 is located within a canonical CA element, with a GU-rich region starting 13 nt downstream from the TES. The NTO3 has a CTTAAA poly(A) signal [ 68 ] starting 20 nt upstream from its TES, with a cleavage site in a homopolymer C run and with a consensus GU-rich region starting 25 nt downstream from the TES. The NTO4 has an ATATAA poly(A) signal [ 69 ] starting 24 nt upstream the TES, the cleavage site being marked by a consensus CA signal, followed by a GU-rich region 33 nt downstream.…”
Section: Resultsmentioning
confidence: 99%
“…Our in silico analysis revealed that the poly(A) cleavage site of NTO2 is located within a canonical CA element, with a GU-rich region starting 13 nt downstream from the TES. The NTO3 has a CTTAAA poly(A) signal [ 68 ] starting 20 nt upstream from its TES, with a cleavage site in a homopolymer C run and with a consensus GU-rich region starting 25 nt downstream from the TES. The NTO4 has an ATATAA poly(A) signal [ 69 ] starting 24 nt upstream the TES, the cleavage site being marked by a consensus CA signal, followed by a GU-rich region 33 nt downstream.…”
Section: Resultsmentioning
confidence: 99%
“…We used the number of pseudo-PASs as a proxy for the expected number of PASs under no selection, where pseudo-PASs are PAS hexamers identified from the complementary sequence of the region of mRNA where PASs are searched. We were able to test these predictions in humans, thanks to a recent study that computationally identified all PASs and pseudo-PASs in human genes (Kainov et al, 2016). The mean number of PASs per gene in the 21,458 human genes examined is 1.87, significantly lower than the mean number of pseudo-PASs per gene (3.85; P < 10 −125 , paired t -test).…”
Section: Resultsmentioning
confidence: 99%
“…The PAS hexamers and pseudo-PASs in human genes, as well as human SNP densities, were acquired from Kainov et al (2016). Briefly, Kainov et al downloaded the PAS hexamers from PAS.db2 (Lee et al, 2007) and converted the genomic coordinates of PASs from hg17 to hg19 using liftOver from UCSC.…”
Section: Star Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcription termination can also occur anywhere from the 3′ end of the mRNA by readthrough transcription ( Proudfoot 1989 ; Dye and Proudfoot 1999 ; Richard and Manley 2009 ), which generates the mRNA 3′ end polymorphism ( de Klerk and ‘t Hoen 2015 ; Kainov et al 2016 ; Nourse et al 2020 ). In yeast, various transcript boundaries are present ( Gullerova and Proudfoot 2008 ; Pelechano et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%